1999
DOI: 10.1172/jci5205
|View full text |Cite
|
Sign up to set email alerts
|

Novel insight from transgenic mice into thyroid hormone resistance and the regulation of thyrotropin

Abstract: Patients with resistance to thyroid hormone (RTH) exhibit elevated thyroid hormone levels and inappropriate thyrotropin (thyroid-stimulating hormone, or TSH) production. The molecular basis of this disorder resides in the dominant inhibition of endogenous thyroid hormone receptors (TRs) by a mutant receptor. To determine the relative contributions of pituitary versus hypothalamic resistance to the dysregulated production of thyroid hormone in these patients, we developed a transgenic mouse model with pituitary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 53 publications
2
39
0
2
Order By: Relevance
“…If NCoR binding to the TR limits ligand-independent activation, then the inability of the R429 mutant to bind NCoR may help explain the enhanced ligandindependent activation seen in the presence of this mutation. This potential mechanism for enhanced ligand-independent activation is consistent with the finding of impaired ligand-independent activation in mice with pituitary-specific expression of ⌬337T, a GRTH mutant TR that constitutively binds to NCoR (55). Consistent with our findings with liver Gsta, Astapova et al (41) recently found that ligand-independent activation of hepatic TH target genes did not seem to be significantly affected by expression of L-NCoR⌬ID.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…If NCoR binding to the TR limits ligand-independent activation, then the inability of the R429 mutant to bind NCoR may help explain the enhanced ligandindependent activation seen in the presence of this mutation. This potential mechanism for enhanced ligand-independent activation is consistent with the finding of impaired ligand-independent activation in mice with pituitary-specific expression of ⌬337T, a GRTH mutant TR that constitutively binds to NCoR (55). Consistent with our findings with liver Gsta, Astapova et al (41) recently found that ligand-independent activation of hepatic TH target genes did not seem to be significantly affected by expression of L-NCoR⌬ID.…”
Section: Discussionsupporting
confidence: 93%
“…Although CRTH is sometimes referred to as pituitary RTH (PRTH), we have in the past proposed that CRTH is a more appropriate term because isolated pituitary RTH is unable to elevate TH levels in mice (55). However, like PRTH, CRTH seems to be a misnomer.…”
Section: Discussionmentioning
confidence: 99%
“…The different TR isoforms play distinct roles in endocrine physiology (14,17,(21)(22)(23)(24). The TR␤2 isoform in the hypothalamus and pituitary plays a particularly crucial role in a negative feedback regulatory loop by which increases in circulating T 3 /T 4 thyroid hormone levels result in suppression of thyroid releasing hormone and thyroid stimulating hormone synthesis, thereby restoring proper endocrine homeostasis (19,20,22,(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…The THRB2 isoform participates in the positive and negative regulations of Gh and Tshb expressions, respectively (Abel et al 1999, Barra et al 2004. In humans, mutations in THRB isoforms led to the classic form of resistance to thyroid hormone (RTHB) characterized by high TH levels and normal or slightly elevated serum TSH concentration, due to the resistance of pituitary and hypothalamus to respond to the negative feedback triggered by TH (Forrest et al 1996, Refetoff et al 2014.…”
Section: Nuclear Thyroid Receptors and The Gene Expression Regulationmentioning
confidence: 99%
“…The lack of all THRB isoforms (Thrb −/− ) led to resistance to thyroid hormone (RTH-b) characterized by the enlargement of the thyroid gland (goiter), increased size and number of follicles, elevated T 4 and T 3 concentrations, normal or elevated serum TSH concentration and increased Tshb and Cga mRNA expressions due to defects in thyrotrophic response to THs (Forrest et al 1996, O'Shea & Williams 2002, Mendoza & Hollenberg 2017. The generation of THRB2 knockout (Thrb2 −/− ) mice provided evidence that this isoform plays a major role in the negative feedback exerted by T 3 in thyrotrophs and in the stimulation of Gh mRNA synthesis in somatotrophs (Abel et al 1999(Abel et al , 2003.…”
Section: Negative Transcriptional Regulation Of Cga and Tshb Genes Bymentioning
confidence: 99%